Transcending the culture-nature divide in cultural heritage : views from the Asia-Pacific Region - Brockwell, Sally, 1955-; O'Connor, Sue; Byrne, Denis (Terra Australis ;, 2013)
While considerable research and on-ground project work focuses on the interface between Indigenous/local people and nature conservation in the Asia-Pacific region, the interface between these people and cultural heritage conservation has not received the same attention. This collection brings together papers on the current mechanisms in place in the region to conserve cultural heritage values. It will provide an overview of the extent to which local communities have been engaged in assessing the significance of this heritage and conserving it. It will address the extent to which management regimes have variously allowed, facilitated or obstructed continuing cultural engagement with heritage places and landscapes, and discuss the problems agencies experience with protection and management of cultural heritage places -- Provided by publisher.